Model Pendekatan Bimbingan Konseling dalam Perspektif Teologis Kristen - Purwanto; Leyder, Raymond A. (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
The complexity of life's challenges demands a holistic counseling approach, where Christian counseling offers a theological perspective to understand fundamental human issues, particularly related to human sinfulness and the need for spiritual transformation. Through a library research method with a descriptive qualitative approach, this study explores the history, development, characteristics, and fundamental principles of Christian counseling in a theological context. Data sources were obtained from theological literature, Christian counseling books, scientific journals, and relevant library sources examined in-depth and systematically. The research reveals that Christian counseling has unique characteristics: focusing on God (theocentric), aiming at Imitatio Christi, and oriented towards spiritual transformation through the illumination of the Holy Spirit. Christian counseling is understood not merely as a psychological method, but as a fundamental spiritual calling to restore human relationships with God.